The Transfer Space - Thomas Friedrich (Economics and Econometrics Research Institute (EERI), 2010)
Within the transfer space source and sink exchange substrates (material and energy) to selfishly optimize their own productivity. Under certain conditions this will lead to a productivity increase of the whole ensemble. The present day view that cooperation is the most productive interaction between organisms is an illusion. Whenever two not identically equipped parties meet with the potential to exchange substrates one party will become a source and the other a sink. This is realistically called exploitation. The outcome depends on the relation between fix cost, variable cost, productivity and affinity. Brute force and educational conditioning used by the sink take advantage of emotions to hide the real size of cost to the source in exploitation. In case the transfer of substrates leads to increased productivity parts of the productivity might be reinvested to keep the exploited party. The lasting relationship is called wise exploitation. Wise exploitation may last for one or many generations depending on the use of brute force, education or breeding. All actions have to be viewed under thermodynamic considerations and the benefit must always exceed the cost to maintain a stable system. This hypothesis explains observations from catalytic networks to societies.
Keywords: J10; C70; Q2; 330; Transfer space; symbiosis; productivity; saturation function